Philosophical Personalistic Reflection on the Body as a Contribution to Theology - Granados, José (Teologia w Polsce, 2020)
<span style="background-color: #ffffff; color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">The article explores how Personalist Philosophy can be helpful for Theology by focusing on the concrete topic of the body. The renewed philosophical interest in the body is important for Christian Theology inasmuch as the latter is centered on the concreteness of the Incarnation. The article follows Gabriel Marcel’s approach as a guideline to review the understanding of the body proper to Personalism. In this approach, the body is seen as the person’s relational presence in the world and among others and as the openness of the person towards transcendence. The richness of this approach is explored in three important areas of dogmatic theology: Christology, Sacramentology, and the Theology of Creation. The article exemplifies the circularity between Philosophy and Theology in the concrete topic of the body.